Turkey - Performance Based Contracting Scheme in Family Medicine : Design and Achievements - World Bank (Washington, DC, 2014)
Prior to 2003, health outcomes in Turkey, including maternal and child health outcomes, lagged behind those of Organization for Economic Co-operation and Development (OECD) countries and of those in other middle income countries. This report aims to add to this body of evidence through the conduct of a comprehensive review of the scheme within the context of the overall family medicine program. It describes and assesses Turkey's performance based payment scheme in family medicine with regard to design, institutional arrangements, governance, monitoring and evaluation, implementation, results and financial implications. Potential areas for improvement are identified and further refinements of the current system are suggested. The report will also contribute to the current body of knowledge on the experience with pay for performance in primary care for the interest of other countries. The study methodology uses both quantitative and qualitative approaches. Further as the scheme was rolled out among Turkey's provinces gradually, the quantitative assessment uses before-and-after comparisons for providers/provinces in the scheme as well as comparison of providers/provinces in the scheme and outside the scheme where feasible. Three focus groups were conducted with Family Medicine Practice (FMP) doctors, FMP health personnel and division chiefs (or deputies) from the provincial administration/Community Health Centers (CHC) to obtain their views about the performance-based contracting scheme and to complement the information gathered from other sources.